MIF tautomerase inhibitor TE-11 prevents inflammatory macrophage activation and glycolytic reprogramming while reducing leukocyte migration and improving Crohn’s disease-like colitis in male mice - Vámos, Eszter; Vántus, Viola Bagóné; Deák, Péter; Kálmán, Nikoletta; Sturm, Eva Maria; Nayak, Barsha Baisakhi; Makszin, Lilla; Loránd, Tamás; Gallyas, Ferenc Jr; Radnai, Balázs (Frontiers in Immunology, 2025)
Background & aimsCrohn’s disease (CD) is a chronic inflammatory disorder primarily affecting the gastrointestinal tract. Leukocyte recruitment, M1 macrophage polarization and associated metabolic reprogramming are hallmarks of its pathomechanism. Here, we tested TE-11, a potent MIF tautomerase inhibitor (IC50 = 5.63 μmol/dm3) in experimental Crohn’s disease in male mice, in leukocyte recruitment and in inflammatory M1 macrophage activation.Methods2,4,6-trinitrobenzenesulfonic acid-(TNBS)-induced colitis was utilized as a CD-model in male mice. We performed macroscopic scoring and cytokine measurements. We also analyzed MIF-induced leukocyte migration and evaluated apoptosis. LPS+IFN-γ-induced RAW264.7 cells were applied as a M1 macrophage model. We performed qPCR, ROS and nitrite determinations, ELISA measurements, mitochondrial oxygen consumption rate and extracellular acidification rate determinations.ResultsTE-11 improved mucosal damage, reduced inflammation score and concentration of IL-1β and IL-6 in the colon. It inhibited MIF-induced human blood eosinophil and neutrophil migration and counteracted the anti-apoptotic effect of MIF. In macrophages, MIF inhibition prevented M1 polarization by downregulating HIF-1α gene expression in LPS+IFN-γ-activated cells. Additionally, the molecule reduced mRNA transcription and protein expression of chemokine CCL-2 and cytokine IL-6 while further increasing SOD2 gene transcription and decreased ROS and nitrite production in macrophages. During inflammatory metabolic reprogramming, TE-11 prevented LPS+IFN-γ-induced metabolic shift from OXPHOS to glycolysis. Similarly to anti-inflammatory M2 cells, TE-11 improved mitochondrial energy production by increasing basal respiration, ATP production, coupling efficiency, maximal respiration and spare respiratory capacity.ConclusionComprehensively, TE-11, a MIF tautomerase inhibitor ameliorates CD-like colitis, reduces MIF-induced eosinophil and neutrophil migration and prevents M1 polarization and associated metabolic reprogramming; therefore, it may prove beneficial as a potential drug candidate regarding CD therapy.